N-Nitro-L-Arginine-Methyl ester Exerts Neuroprotection byInhibiting Inflammation in Cerebral Injury Induced by Transient Ischemia/Reperfusion in Rats: Pharmaceutical Science-Psychology for Curing Mental Health - Hiba A Awooda (International Journal of Life Science and Pharma Research, 2022)
Cerebral ischemia-reperfusion injury is a pivotal cause of deaths due to cerebrovascular accidents. Further research efforts are needed to reveal the mechanism underlying its aggravation or alleviation. We previously reported the antioxidant effect of N-Nitro-L-Arginine- Methyl Ester (L-NAME), a nonselective nitric oxide synthase (NOS) inhibitor, on rats subjected to transient focal cerebral ischemia-reperfusion (I/R). The aim of this work was to explore further neuroprotective anti-inflammatory effects of L-NAME. This study involved 30 adult male Wistar rats divided into three groups with ten rats in each: sham-operated (control), I/R group of rats subjected to 30 minutes of left common carotid artery (CCA) occlusion followed by 24-hour of reperfusion and test group infused with L-NAME intraperitoneally 15 minutes before the same I/R period. Neurological assessments were evaluated, Western blotting used to estimate Nuclear factor-kappa B (NF-?B), ELISA used to detect Tumor necrosis factor- α (TNF-α), and Nitric oxide metabolites were measured colorimetrically, as well as H&E staining to assess brain damage. Compared with the I/R group, the neurological score, infarction area, and the inflammatory biomarkers NF-?B, TNF-α, and NO were significantly decreased in L-NAME treated rats (P =0.001). As a conclusion from the current study, L-NAME showed potential neuroprotection through it is an anti-inflammatory effect on a rat’s model of transient focal cerebral ischemia-reperfusion.